FINANCIAL LITERACY AND SAUDI YOUTH - Rida Zahra Khan; Tahar Tayachi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In today's demanding financial environment, it is very important to be acquainted with the knowledge of managing money. Money needs to be earned, invested and saved correctly. Young adults usually tend to find themselves carrying large amount of credit card debt or loans and the inability of managing capital will prevent the aptitude of accumulating wealth. In this research, examined financial literacy rate among the youth of Saudi Arabia was examined using the financial literacy test of FINRA. I showed that the financial literacy is low among the young adults; very few possess basic knowledge of interest rate, inflation, risk diversification, impact that a shorter term can have on total interest payments over the life of a mortgage and the relationship between bond prices and interest rates. Financial education is very important to be taught to young people for financial wellbeing no matter what profession they are in.